OP0214 Investigation of rheumatoid arthritis genetic susceptibility markers in the early rheumatoid arthritis study (ERAS) provides further replication of the TRAF1/C5 association with radiological damage. (23rd January 2014) - Viatte, S.; Plant, D.; Lunt, M.; Fu, B.; Parker, B.; Galloway, J.; Solymossy, C.; Worthington, J.; Symmons, D.; Dixey, J.; Young, A.; Barton, A.
Abstract : Background: A rheumatoid arthritis (RA) susceptibility region between the TNF receptor-associated factor-1 and complement component 5 genes ( TRAF1/C5 ) has previously been reported to associate with radiological damage in two studies. Objectives: We aimed to test rheumatoid arthritis (RA) genetic susceptibility markers for association with a continuous measure of radiological damage over time using longitudinal modelling techniques in a discovery cohort of patients with inflammatory polyarthritis (IP). An independent inception cohort of UK IP patients was used as a replication cohort, and also combined together with the discovery cohort in order to increase sample size and power. Methods: Sixty-seven RA susceptibility variants were genotyped in 474 patients from the Early Rheumatoid Arthritis Study (ERAS) using Sequenom MassArray technology. Correlation between genetic markers and Larsen score, as a time dependent trait, was assessed longitudinally using zero-inflated negative binomial regression to include repeat measurements in the same individual at different time points. Genetic markers associated with radiological damage in ERAS were tested using the same modelling techniques on previously published data from the Norfolk Arthritis Register (NOAR). Finally, the model was adapted to accommodate differences in disease progression between the two cohorts and a combined analysis was performed. Results: rs2900180 at the TRAF1/C5 locus was the single marker associated longitudinally with Larsen score in the ERAS cohort (p=0.02; time averaged effect size: 2.96 Larsen units) and in the NOAR cohort (p=0.04; effect size: 1.56). Analysis of individual time points in ERAS showed that TRAF1/C5 polymorphisms display their effect primarily on the extent of Larsen score early in the disease course (rs2900180, year 2: coef. 0.35 95%CI 0.04, 0.66, p=0.025; rs10760130, year 2: coef. 0.34 95%CI 0.03, 0.65, p=0.030). Combined longitudinal analysis of the two cohorts suggests further association of several loci with Larsen score ( KIF5A, PTPN22, AFF3, TAGAP ). Conclusions: The genetic marker rs2900180 is associated with extent of erosions, as measured by the Larsen score, in the ERAS cohort. This represents the third independent study correlating genotype at the TRAF1/C5 locus with radiological severity in RA. Replication in a large dataset is required to establish the role of other RA susceptibility loci in disease severity. Disclosure of Interest: None Declared